Delirium risk stratification in consecutive unselected admissions to acute medicine: validation of externally derived risk scores - Pendlebury, S; Lovett, N; Smith, S; Cornish, E; Mehta, Z; Rothwell, P (Oxford University Press, 2016)
reliable delirium risk stratification will aid recognition, anticipation and prevention and will facilitate targeting of resources in clinical practice as well as identification of at-risk patients for research. Delirium risk scores have been derived for acute medicine, but none has been prospectively validated in external cohorts. We therefore aimed to determine the reliability of externally derived risk scores in a consecutive cohort of older acute medicine patients.consecutive patients aged ≥65 over two 8-week periods (2010, 2012) were screened prospectively for delirium using the Confusion Assessment Method (CAM), and delirium was diagnosed using the DSM IV criteria. The reliability of existing delirium risk scores derived in acute medicine cohorts and simplified for use in routine clinical practice (USA, n = 2; Spain, n = 1; Indonesia, n = 1) was determined by the area under the receiver operating characteristic curve (AUC). Delirium was defined as prevalent (on admission), incident (occurring during admission) and any (prevalent + incident) delirium.among 308 consecutive patients aged ≥65 (mean age/SD = 81/8 years, 164 (54%) female), existing delirium risk scores had AUCs for delirium similar to those reported in their original internal validations ranging from 0.69 to 0.76 for any delirium and 0.73 to 0.83 for incident delirium. All scores performed better than chance but no one score was clearly superior.externally derived delirium risk scores performed well in our independent acute medicine population with reliability unaffected by simplification and might therefore facilitate targeting of multicomponent interventions in routine clinical practice.